Energy transfer from phycobilisomes to photosystem I at room temperature - Biswas, Avratanu; Akhtar, Parveen; Lambrev, Petar H.; van Stokkum, Ivo H.M. (Frontiers in Plant Science, 2024)
The phycobilisomes function as the primary light-harvesting antennae in cyanobacteria and red algae, effectively harvesting and transferring excitation energy to both photosystems. Here we investigate the direct energy transfer route from the phycobilisomes to photosystem I at room temperature in a mutant of the cyanobacterium Synechocystis sp. PCC 6803 that lacks photosystem II. The excitation dynamics are studied by picosecond timeresolved fluorescence measurements in combination with global and target analysis. Global analysis revealed several fast equilibration time scales and a decay of the equilibrated system with a time constant of ≈220 ps. From simultaneous target analysis of measurements with two different excitations of 400 nm (chlorophyll a) and 580 nm (phycobilisomes) a transfer rate of 42 ns -1 from the terminal emitter of the phycobilisome to photosystem I was estimated.